2012
DOI: 10.1136/bjsports-2012-091046
|View full text |Cite
|
Sign up to set email alerts
|

Illness during the 2010 Super 14 Rugby Union tournament – a prospective study involving 22 676 player days

Abstract: Infective illness involving the respiratory tract and gastrointestinal tract together with dermatological illness was common in elite rugby players participating in this international tournament. A delay in reporting of symptoms >24 h could have important clinical implications in player medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 25 publications
4
76
4
1
Order By: Relevance
“…In our study, we report the IR of illness and, therefore, our data can be compared with other studies where IR was also reported. The IR of illness in Paralympic athletes is higher than that reported for some,3 9 but not all studies 5 8. It should, however, be noted that these data are from able-bodied athletes participating in single sports codes (football and rugby union).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In our study, we report the IR of illness and, therefore, our data can be compared with other studies where IR was also reported. The IR of illness in Paralympic athletes is higher than that reported for some,3 9 but not all studies 5 8. It should, however, be noted that these data are from able-bodied athletes participating in single sports codes (football and rugby union).…”
Section: Discussionmentioning
confidence: 63%
“…However, in comparison to injury, illness has been less commonly studied during major competitions. Illness surveillance studies have only recently been conducted during major international competitions such as the 2009 IAAF World Athletic championship,3 the 2009 FINA (aquatic) World championships,4 the 2009 Confederations Cup Football tournament,5 the 2010 Vancouver Winter Olympic Games,6 the 2010 Super 14 Rugby Union tournament,7 8 the 2010 FIFA World Cup9 the 2010 Asian Beach Games10 and most recently, the 2012 Youth Olympic Games 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, regular national and international travel is common, with a wide range of between-match intervals, time zone changes also commonplace. Consequently, in addition to fatigue-related performance attenuation effects, health challenges such as an increased incidence of gastrointestinal and respiratory illness are often faced by teams (Schwellnus et al, 2012). Previous research has looked to formally address some of these influences in informing tactical periodisation design, through the development of match difficulty ratings (Kelly & Coutts, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…moderate loads reduce the infection risk and heavy, intense exertions increase that risk. That view was supported by authors who reported URTI to be particularly abundant in competitive athletes [13,37,41,49,51]; highest relative incidence of URTI was noted at Winter Olympics [14,22,48], Summer Olympics [49,58] and at World Championships [1,2,13]. It ought to be noted that asthma, allergic rhinitis, exercise-induced bronchial spasm and hyperventilation may produce URTI-like symptoms thus making detection of URTI very difficult.…”
Section: Effects Of Urti On Motor Activitiesmentioning
confidence: 94%